Daya Tarik Wisata Religi Berbasis Budaya Lokal: Studi Pada Tradisi Rajaban Desa Prawoto - Shofi’unnafi Shofi’unnafi (UIN Siber Syekh Nurjati Cirebon, 2021)
Local culture is one of the tourist attractions that can attract tourists to visit a tourist destination. Currently, local culture is able to contribute for increasing trend of religious tourism with various uniqueness and characteristics. The study was conducted to find out in depth the potential of local culture in the Rajaban tradition to attract tourists for making religious trips in Prawoto Village. This study uses qualitative research methods with data collection techniques through interviews and field observations. The results showed that the local culture performed in the Rajaban tradition has an attraction for tourists who go on religious trips because 1) tourists see the excitement of the carnival featuring various traditional art performances such as barongan, jaranan, tambourine and ogoh-ogoh carnival. 2) Tourists can simultaneously make pilgrimages to the tomb of Sunan Prawoto to fulfill spiritual needs and increase piety. 3) Tourists can buy various souvenirs and culinary delights to be used as souvenirs at the night market which is only available in the month of Rajab.